Children in Moral Danger and the Problem of Government in Third Republic France - Schafer, Sylvia (Book collections on Project MUSE., 2015)
By exploring how children and their families became unprecedented objects of governmental policy in the early decades of France's Third Republic, Sylvia Schafer offers a fresh perspective on the self-fashioning of a new governmental order. In the aftermath of the Franco-Prussian War, social reformers claimed that children were increasingly the victims of their parents' immorality. Schafer examines how government officials codified these claims in the period between 1871 and 1914 and made the moral status of the family the focus of new kinds of legislative, juridical, and administrative action.